Delineation of the aquifer structure and estimation of hydraulic properties on the flanks of Mount Meru, Northern Tanzania. (December 2022) - Bennett, George; Van Camp, Marc; Shemsanga, Ceven; Kervyn, Matthieu; Walraevens, Kristine
Abstract: Understanding of the aquifer structure and its hydraulic properties provides comprehensive knowledge for proper groundwater utilisation and management. This study delineated the aquifer structure using litho-hydrostratigraphical cross-sections, and estimated the hydraulic parameters using single well pumping tests for various locations on and around Mount Meru. Results show that, the aquifer system on the flanks of Mount Meru is a sloping aquifer with sloping beds. On the far east of the eastern flank, the aquifer is composed of debris avalanche deposits, while on the north-eastern and west flanks the aquifer is composed of weathered fractured lava, whereas on the south-western flank, the aquifer is composed of different layers: pyroclastics on the top, weathered fractured lava, weathered pyroclastics, and weathered fractured lava at the bottom. The aquifer is semi-confined on the north-eastern and western flanks; on the north-eastern flank, the overlying debris avalanche deposits acting as an aquitard, while on the western flank, the overlying layers: pyroclastics and unweathered lava acting as an aquitard and aquiclude, respectively. The aquifer is unconfined on the far east of the eastern flank and south-western flank. The transmissivity of the aquifer on the north-eastern flank is substantially increasing with increasing depth, while variable, both at the shallow depth of hand-dug wells and the larger depth of boreholes, on the south-western flank; indicating aquifer heterogeneity. On the north-eastern flank, the topmost part of the aquifer, exploited by hand-dug wells, has a low transmissivity (T = 1.3 m 2 /d) and potential for smaller withdrawals for local water supply with limited consumption, while the upper part of the aquifer, captured by boreholes, has an intermediate transmissivity (T = 35 m 2 /d) and potential for local water supply, whereas the deeper part of the aquifer has a high transmissivity (T = 788 m 2 /d) with potential of somewhat regional importance. On the western flank, the aquifer has a very low transmissivity (T = 0.4 m 2 /d) and potential for local water supply with limited consumption. On the south-western flank, on average, the topmost part of the aquifer, exploited by hand-dug wells, has very low to intermediate transmissivity (range of T: 0.3–21 m 2 /d), leading to variable potential for smaller withdrawals for local water supply (private consumption), whereas the deeper part of the aquifer, captured by boreholes, has low to intermediate transmissivity (range of T: 9–43 m 2 /d) and potential for local water supply. Graphical abstract: Image 1 Highlights: Volcanic aquifer system. Sloping aquifer with sloping beds. The transmissivity of the aquifer on the north-eastern flank is substantially increasing with increasing depth. The transmissivity of the aquifer is variable, both at the shallow depth and the larger depth on the south-western flank. The aquifer system has variable potential.